2019
DOI: 10.1177/1534735419886655
|View full text |Cite
|
Sign up to set email alerts
|

Functional Regulation of Ginsenosides on Myeloid Immunosuppressive Cells in the Tumor Microenvironment

Abstract: Ginsenosides, the key components isolated from ginseng, have been extensively studied in antitumor treatment. Numerous studies have shown that ginsenosides have direct function in tumor cells through the induction of cancer cell apoptosis and the inhibition of cancer cell growth and enhance the antitumor immunity through the activation of cytotoxic T lymphocytes and natural killer cells. However, little is known about the function of ginsenosides on myeloid immunosuppressive cells including dendritic cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Ginsenosides, the main active ingredient of ginseng, have significant anticancer activity by inhibiting cell proliferation, promoting apoptosis, inducing cell cycle arrest of cancer cells, inhibiting tumor angiogenesis, and synergizing with chemo-/radiotherapy [245]. Besides, ginsenosides can activate the body's immunity through different ways to fight against cancer [246]. Some kinds of ginsenosides are undergoing clinical trials [247].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Ginsenosides, the main active ingredient of ginseng, have significant anticancer activity by inhibiting cell proliferation, promoting apoptosis, inducing cell cycle arrest of cancer cells, inhibiting tumor angiogenesis, and synergizing with chemo-/radiotherapy [245]. Besides, ginsenosides can activate the body's immunity through different ways to fight against cancer [246]. Some kinds of ginsenosides are undergoing clinical trials [247].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Our previous data demonstrated that some of Ginsenosides isolated from Panax ginseng C. A. Mey. were able to convert TAM polarization from M2-like to M1-like to attenuate tumor metastasis ( Zhang Y. et al, 2019 ). Recently, Panax ginseng C. A. Mey.-derived nanoparticles (PGDN) were also found to have similar regulatory roles on TAMs in melanoma.…”
Section: The Impact Of Chm and Their Active Ingredients On Timps In Tmentioning
confidence: 99%
“…Our recent report has shown that Ginsenosides, as the functional contents of ginseng, enhance the antigen presentation function of DCs within the TME. Ginsenosides activate the activity of DCs and promote adaptive immune responses to exert anticancer effects in tumor-bearing mice ( Zhang Y. et al, 2019 ). Both the purified glycyrrhizin (GL) and Carthamus tinctorius L. (CT) extract stimulate DC maturation to bolster antitumor activity.…”
Section: The Impact Of Chm and Their Active Ingredients On Timps In Tmentioning
confidence: 99%
“…Tumour‐immune cells interaction is a significant territory of research in regard to prognosis in CRC. Cancer accelerating inflammation orchestrates a strong immune cell response and the tumour microenvironment (TME) are arising as crucial obstacles to the development of effective therapies 6,7 . Specifically, tumour‐associated macrophages (TAMs) are dominating immune cells in the TME and have been implicated in neoplastic progression, survival and metastatic dissemination in various solid tumours 8,9 .…”
Section: Introductionmentioning
confidence: 99%